Penyelesaian Perselisihan Perdata Masyarakat Desa Menurut Undang-Undang Nomor 6 Tahun 2014 tentang Desa - Disca Yuli Ika Prabawati (Universitas Islam Balitar, Blitar, 2019)
This study is based on the fact that a village head's demands must be able to resolve problems and disputes in his area because actually conflicts or disputes are normal and inevitable as long as there is interaction between humans. This research tries to answer about the authority and role of the Village Chief in resolving civil society disputes according to Law Number 6 Year 2014 concerning Villages and what are the obstacles faced by the Village Head in resolving Village Community disputes and how the solutions are offered. The method used is a normative juridical method in this case is research conducted by examining the substance of legislation on the subject matter. The results of this study indicate that based on Article 26 (4) letter K of Act Number 6 of 2014 concerning Villages, the village head is obliged to resolve community disputes in the village. There are obstacles that hinder the process of resolving disputes properly, one of which is poor quality human resources. The solution offered is to improve the quality of human resources.